2021
DOI: 10.1039/d1em00087j
|View full text |Cite
|
Sign up to set email alerts
|

Fates and spatial variations of accumulation mode particles in a multi-zone indoor environment during the HOMEChem campaign

Abstract: We report on significant spatial gradients of accumulation mode particles emitted during the HOMEChem campaign and assess particle loss pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…This is likely due to PM 2.5 emissions during cooking activities increasing concentrations in the kitchen, which are then diluted and lost to surface deposition and exfiltration during transport to the bedroom. 70,71 During the nighttime (Fig. 6), this difference dropped to 0–23%, which further confirms the hypothesis that the differential is driven by cooking activities.…”
Section: Resultssupporting
confidence: 78%
“…This is likely due to PM 2.5 emissions during cooking activities increasing concentrations in the kitchen, which are then diluted and lost to surface deposition and exfiltration during transport to the bedroom. 70,71 During the nighttime (Fig. 6), this difference dropped to 0–23%, which further confirms the hypothesis that the differential is driven by cooking activities.…”
Section: Resultssupporting
confidence: 78%
“…Surfaces are more prevalent in indoor spaces compared to outdoor environments, with a typical surface area to volume ratio of 3 m –1 , comprising a larger fraction of the overall space. Surfaces influence a range of physical and chemical processes, acting as a sink for deposited aerosols, partitioning of gaseous compounds, , and the formation of new species through surface-mediated reactions or heterogeneous reactions with trace indoor gases. , The composition and morphology of surfaces are highly diverse, and their evolution depends largely on location and the emission sources nearby. Modeling and field measurements have shown that thin films and particulate matter cover the surface over time. ,,, In the absence of external perturbations, these films and deposited aerosols can remain on surfaces for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any mass loss is driven solely by dilution-driven evaporation. It has been previously shown that deposition and exfiltration (not including venting through window-or door-opening) are too slow to account for spatial variations in particle concentration throughout a house, making dilution the dominate driver of these spatial variations 56 . For simplicity, we therefore assume no losses from deposition or exfiltration.…”
Section: Dilution-driven Evaporationmentioning
confidence: 99%